2008
DOI: 10.1111/j.1365-2036.2008.03648.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: use of antitumour necrosis factor therapy in inflammatory bowel disease during pregnancy and conception

Abstract: Summary Background  One of the most frequently asked questions during consultation with those affected by inflammatory bowel disease is what are its effects on pregnancy, and how the treatment will impact on conception and pregnancy outcomes. Aim  To review available data regarding the safety of biological therapies during pregnancy, primarily in woman with inflammatory bowel disease. Methods A Medline search was performed and available original research and review articles relating to the use of biological (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…There is still no evidence today that intentional anti-TNF treatment is safe in pregnancy, as only 33 mothers including the case we are reporting herein have continued their treatment during the second and/or third trimester [7], when there is increasing transplacental transport of IgG antibodies [19]. Since the efficiency of transplacental transport of IgG is poor until the late second or early third trimester, limiting the use of infliximab to the first 30 weeks of pregnancy has been recommended [15]. In 3 patients with Crohn’s disease who received infliximab until approximately gestational week 30 and resumed infliximab treatment within 3–14 days after giving birth, infliximab was undetectable in the sera of newborn children or in the breast milk of nursing mothers [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is still no evidence today that intentional anti-TNF treatment is safe in pregnancy, as only 33 mothers including the case we are reporting herein have continued their treatment during the second and/or third trimester [7], when there is increasing transplacental transport of IgG antibodies [19]. Since the efficiency of transplacental transport of IgG is poor until the late second or early third trimester, limiting the use of infliximab to the first 30 weeks of pregnancy has been recommended [15]. In 3 patients with Crohn’s disease who received infliximab until approximately gestational week 30 and resumed infliximab treatment within 3–14 days after giving birth, infliximab was undetectable in the sera of newborn children or in the breast milk of nursing mothers [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a series of 10 pregnancies in women with Crohn’s disease who were intentionally treated with infliximab, all pregnancies ended in live births, with no congenital malformations or intrauterine growth retardation [14]. A recent review on the use of anti-TNF therapy in inflammatory bowel disease during pregnancy and conception concluded that it appears to be safe in pregnancy, even though most studies are confounded by the fact that most patients are on multiple medications and have varying levels of disease activity [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Animal studies provide no evidence for embryotoxicity and teratogenicity. Post-marketing data report a significant number of normal pregnancies; however, a few adverse outcomes have been observed as well [35,36] . Because of limited data regarding the safety of infliximab, the manufacturer recommends adequate contraception.…”
Section: Immunosuppressive Therapy In Pregnant Ibd Patientsmentioning
confidence: 99%
“…It is classified as FDA class B drugs for use during pregnancy. There are few isolated reports of associated malformations (53) , but most studies have been favorable to its use in period (43) . What is known, however, is that efforts should be made to control the IBD during pregnancy, as activities with greater intensity may put at risk both the mother and the fetus.…”
Section: E) Biological Therapymentioning
confidence: 99%